Dense non‐Newtonian suspension flow: Effect of solids properties and pipe size. Issue 8 (25th March 2022) - Zheng, Enzu; Rudman, Murray; Kuang, Shibo; Chryss, Andrew
Abstract: High concentration tailings transport is a promising approach for improving the safety and environmental impact of mining tailings disposal. High concentration suspensions exhibit complex non‐Newtonian behavior. The interaction between the non‐Newtonian carrier and the coarse particles is still poorly understood, particularly in the turbulent regime. This article considers the effect of solids concentration, particle and pipe size on transport characteristics in a weakly turbulent non‐Newtonian suspension using a DNS‐DEM methodology. Heterogeneous flow and a sliding bed are presented in the turbulent regime, with particles being more suspended in a small pipe. Although stratification is observed, there is no "packed" bed predicted for these cases. The presence of the viscous core region contributes to the dominance of the drag force in the central region in a non‐Newtonian suspension. Non‐Newtonian suspensions can also be transported at a much lower velocity and display a comparable specific energy consumption to a conventional dilute suspension.